2022
DOI: 10.3389/fimmu.2022.867716
|View full text |Cite
|
Sign up to set email alerts
|

High Titers of Low Affinity Antibodies in COVID-19 Patients Are Associated With Disease Severity

Abstract: BackgroundAlmost 2 years from the beginning of the coronavirus disease 2019 (COVID-19) pandemic, there is still a lot unknown how the humoral response affects disease progression. In this study, we investigated humoral antibody responses against specific SARS-CoV2 proteins, their strength of binding, and their relationship with COVID severity and clinical information. Furthermore, we studied the interactions of the specific receptor-binding domain (RBD) in more depth by characterizing specific antibody respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Our results are in line with the findings of Hendriks et al's study that reported a correlation between high levels of antibodies with low affinity and disease severity in COVID-19 patients [3]. Similar to our study, they found a significantly higher antibody titers against SARS-CoV-2 antigens (RBD, N, S1 and S1S2) in hospitalized or critically ill patients compared to mild patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with the findings of Hendriks et al's study that reported a correlation between high levels of antibodies with low affinity and disease severity in COVID-19 patients [3]. Similar to our study, they found a significantly higher antibody titers against SARS-CoV-2 antigens (RBD, N, S1 and S1S2) in hospitalized or critically ill patients compared to mild patients.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the literature, COVID-19 reinfection cases are not so infrequent that according to a study on healthcare workers in Chicago, up to 2.5% of subjects, within a 6-month follow-up, presented a probable SARS-CoV-2 reinfection [2]. Even after more than 2.5 years of SARS-CoV-2 global spread and intensive scientific efforts, many questions on specific patient factors determining disease severity, underlying pathology and the protective/damaging roles of humoral immune responses have remained to be fully addressed [3]. As a notable feature of COVID-19, affected patients exhibit a large heterogeneity in Edited by Matthias J. Reddehase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective efficacy by vaccine-induced antibodies against emerging variants may be impacted by both specific amino acid mutations in the spike and the affinity of the polyclonal antibodies against the SARS-CoV-2 variants. An association was observed between high titers of low-affinity antibodies against RBD with the disease severity of COVID-19 patients 35 . In previous studies, we had demonstrated a strong correlation between antibody affinity and protection from highly pathogenic avian influenza viruses 36 , 37 and a correlation with clinical benefit in patients infected with Zika virus 38 , Ebola virus 10 , influenza virus 39 and COVID-19 8 , 14 .…”
Section: Discussionmentioning
confidence: 90%
“…Similar levels of Ab binding to both Ep9 and EpNeu in the subset of hospitalized and ICU-admitted patients could suggest impaired affinity maturation in patients with more severe outcomes. Impaired Ab affinity maturation have been previously shown to correlate with COVID-19 severity [ 23 , 24 ]. While multiple factors may lead to disease severity during COVID-19, our results suggest that a reliance on high levels of imprinted influenza Abs by a subset of COVID-19 patients could be indicative of a less effective immune response and consequently more severe disease outcomes.…”
Section: Resultsmentioning
confidence: 99%